The Teaching of Arabic in the Ottoman Madrasa Tradition: Why was Spoken Practice Excluded from the Curriculum? - Meydanoglu, Ayse (Anadolu Ilahiyat Akademisi, 2025)
Purpose: The objective of this study is to scertain the reasons why practical Arabic conversation (muhadese) lessons were excluded from the curriculum of Ottoman madrasas. In this regard, the relationship between the objectives of Arabic language teaching and the course structure is examined, and the educational and institutional reasons for the exclusion of practical conversation from the curriculum are discussed; the implications of the absence of muhadese on language practice acquisition are evaluated. Method: The research was conducted within a qualitative framework; sources, academic studies, and historical documents relating to the Ottoman period were compiled through a literature review. These texts subjected to content analysis in order to ascertain information regarding madrasa curricula and teaching practices. The findings were interpreted with reference to the historical context and educational priorities of the period. Findings: The findings demonstrate that Arabic was positioned in madrasas as an 'instrumental science' serving the understanding of Islamic sciences, and that its teaching was structured around the axes of sarf-nahiv and belagat. This approach emphasised teaching centred on reading, comprehension and translation through the explanation of grammar and its application to texts, rather than the four core skills of modern language teaching. Although Arabic texts were read in class, explanations were mostly provided in Turkish, and the emphasis on 'grammar/translation' meant that speaking was not an institutional goal. Whilst lectures (wherein the teacher provides a comprehensive explanation of the text) constituted the primary component of lessons, ancillary activities such as repetition, question-and-answer sessions, and debates played a subsidiary role. The assertion that this practice 'prevented Arabisation' has been the subject of debate, yet no definitive evidence has been found to support this claim. Moreover, it has been observed that, despite the pervasive influence of political authority, the available data is inadequate to suggest the presence of ideological interference in Arabic course content. Conclusion: The present study makes a significant contribution to the existing literature on the subject by offering an explanation for the absence of muhadese lessons in Ottoman madrasas. madrasas. This explanation is based on the premise that Arabic's position as an instrumental science in conjunction with the prevailing book/commentary-centred teaching system, naturally resulted in the absence of muhadese lessons. The study refrains from reducing this phenomenon to claims of 'neglect' or 'prohibition'. The findings indicate that the objective (text comprehension/scientific reading) determines the method in language teaching, suggesting that text analysis and speaking-listening skills should be balanced according to the objective in contemporary theology and Arabic programmes. Future studies may include a comparison of different madrasa regions, an examination of teaching practices in greater detail using archival documents, and an exploration of opportunities for spoken Arabic practice outside the madrasa environment.
Keywords: Arabic Language and Rhetoric; Ottoman Madrasas; Arabic Language Teaching; Muhadese/Conversation Lessons; Language Education; Educational Policies